25 management lessons from the customer's side of the counter - Donnelly, James H (New York McGraw Hill, 1996)
The author relates true-life experiences dealing with a variety of organizations to present valuable lessons in satisfying customers and managing people.
Age Group: Adult
Originally published as: Close to the customer : 25 management tips from the other side of the counter. Homewood, Ill. : Business One Irwin, c1992.
Keywords: Consumer Satisfaction; Customer Services -- Management; Leadership; Supervision of employees